Dynamic intracochlear pressure measurement during cochlear implant electrode insertion. (3rd October 2019) - Ordonez, F.; Riemann, C.; Mueller, S.; Sudhoff, H.; Todt, I.
Abstract: Background: Electrode insertion into the cochlea can cause significant pressure changes inside the cochlea with assumed effects on the cochlea's functionality regarding residual hearing. Model-based intracochlear pressure (ICP) changes were performed statically at the cochlear helix. Aims/objectives: The aim of this study was to observe dynamic pressure measurements during electrode insertion directly at the cochlear implant electrode. Material and methods: The experiments were performed in an uncurled cochlear model that contained a volume value equivalent to a full cochlea. A microfibre pressure sensor was attached at one of two positions on a cochlear implant electrode and inserted under different insertional conditions. Results: We observed the ICP increase depending on the insertional depth. A sensor-position-specific pressure change is insertional-depth dependent. Interval insertion did not lead to a lower peak insertional ICP. Conclusions and significance: In contrast to the static pressure-sensor measurement in the artificial model's helix, a dynamic measurement directly at the electrode shows the pressure profile to increase based on the insertional depth. A mechanical traumatic relevance of the observed pressure values cannot be fully excluded.